STUDY OF MINERAL AND FLAVONOID COMPOSITION OF POMEGRANATE FRUIT (Scientific journal of the Fergana State University, 2025)
In this article presents, the results of a study of the mineral and flavonoid composition of pomegranate fruits grown in the Fergana region. As a result of studying the mineral composition of pomegranate seeds using inductively coupled plasma mass spectrometry, the amount of 32 elements was determined. The total amount of minerals detected was 10388.204 mg/l. The following macroelements were found in pomegranate seeds: calcium, potassium, magnesium, and sulfur. The macroelements calcium and potassium were found in an amount of 9532.36 mg/l, which is 92.4% of the total mass of minerals. The following microelements were determined: Fe, Si, Mn, Al, Zn, Ba, Ti, Cu, B, Sr, Mo, and Rb. Flavonoids contained in pomegranate peel were studied using high-performance liquid chromatography. Rutin was determined in the pomegranate peel in an amount of 8.87 mg/100 g. According to the results of the research, it can be noted that pomegranate seeds are rich in calcium and potassium.